A Juridical Analysis of the Use of Technology in Investigation and Inquiry Processes Based on Scientific Crime Investigation to Uncover the Murder Case of a Former Member of the Langkat Regional House of Representatives - Syaiful Bahri; Triono Eddy (Journal of Legal and Cultural Analytics, 2026)
The development of information technology has brought significant changes to the criminal justice system in Indonesia, particularly in the investigation and inquiry stages of criminal acts. This study aims to analyze the legal basis for the use of technology in the investigation and inquiry process, its application in solving the murder case of a former member of the Langkat Regional People's Representative Council (DPRD), and the validity of technological evidence in the evidentiary process according to criminal procedural law. This study uses a normative-empirical legal method with a conceptual approach and a case approach. Data were obtained through a literature review of primary, secondary, and tertiary legal materials, and supported by an analysis of the practice of applying technology in investigations. The results of the study indicate that the use of technology in investigations and inquiries has a legal basis sourced from the Criminal Procedure Code, the Electronic Information and Transactions Law, and the Police Law. In practice, technologies such as CCTV, telecommunications data, and digital forensics play an important role in helping investigators uncover crimes more objectively and accurately. Legally, technological evidence is basically legitimate for use in the criminal evidentiary process as long as it is obtained through legal procedures, its authenticity and integrity are maintained, and it meets the principles of legality, authenticity, and integrity.